Prorogacija mednarodne pristojnosti - Kramberger Škerl, Jerca (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2012)
In private international law, choice of court agreements (CCAs) represent a departure from the rules on international jurisdiction contained in national and international legal acts. The author analyses the provisions on CCAs in Slovenian private international law. She deals with the reasons for concluding CCAs, the possible content of a CCA, the effects of a CCA, the conditions for the admissibility and validity of such agreements and the applicable law. Furthermore, jurisdiction based on the defendant's appearance, as well as the effects of CCAs in more complex legal relationships, such as in the case of the participation of third parties and related actions are discussed. Special attention is drawn to situations wherein upholding the CCA would lead to undesired results; such situations are analysed from the point of view of general legal principles and the right to a fair trial.
Keywords: mednarodno zasebno pravo; sodišča; pristojnosti; sporazumi